Nostradamus - Dimsdale, Oliver.; Fox, Kerry.; Higgins, Bryn.; Vogel, Hal. (Mentorn Barraclough Carey : distributor Discovery Communications, 2006)
Visiones y pruebas de un futuro espantoso que se hizo el misterio más famoso de todo el mundo.